Speech acts in trial at the district attorney’s office - Nurhasanah, Nurhasanh; Sulistyo, Bambang; Erwanto , Erwanto; Nilawijaya, Rita; Contesa, Emilia (Universitas Jambi, Indonesia, 2026)
This study examines the types of speech acts that occur during trials at the Baturaja OKU District Attorney's Office, utilizing Austin and Searle's speech act theory and Sperber and Wilson's relevance theory. A qualitative approach was adopted, gathering data through observation and interviews with judges, prosecutors, lawyers, witnesses, and defendants. The findings reveal that locutionary speech acts, which convey information, are prominent in the trial setting. Illocutionary speech acts, such as orders, clarifications, and emotional expressions, were used to achieve specific communicative purposes. Perlocutionary speech acts, which provoke emotional responses or actions, significantly influence the behavior of trial participants. The study highlights the impact of the legal context on the interpretation of these speech acts, emphasizing the importance for legal professionals to be proficient in both legal terminology and the nuances of communication. These dynamics contribute to the effectiveness and fairness of the legal process.